Peningkatan Kecerdasan Terhadap Kinerja SDM Dengan IT Sebagai Variabel Moderating - Annisa Qurrota A'yun (Jurnal Manajemen dan Bisnis, 2020)
This study aims to analyze the influence of intellectual, emotional, spiritual intelligence on HR performance with IT being moderate in an agency. The discussion of the importance of the influence of IT with intelligence to improve HR performance has been widely discussed in several literature studies. Although there are many other factors that affect the performance of primary schools, this study only discusses the existence of trust and commitment as determinants of HR performance. Data obtained from 63 respondents using a questionnaire. Data analysis using SPSS 17 shows that the performance of human resources in the agency can be improved by paying attention to the intelligence level of employees towards the agency. Intellectual, emotional, spiritual intelligence with IT as moderate have a positive and significant effect on HR performance.